The Effect of Caffeine Consumption on Sleep Quality among Undergraduate Students in Malaysia - Khairul Ikram, Emmy Hainida; Rosli, Nur Afifah; Hussin, Azizah Mat; Chasni, Atiyah Nurjannah (Jurnal Gizi dan Pangan, 2024)
This study aims to determine the effect of caffeine consumption on sleep quality among university students. This was a cross-sectional study that used a quantitative approach method. The data for this study was collected using a structured online questionnaire and distributed via online platforms to identify eligible participants. All the participants self-administered all three sections of the questionnaire, which were sociodemographic variables, the caffeine questionnaire tool, and the Pittsburgh Sleep Quality Index (PSQI). A chi-squared test was used to investigate the association between caffeine intake and sleep quality and the measured study characteristics. About 300 students, with a mean age of 21.95±1.43 years old, were recruited. The average caffeine intake of the study population was 193.54 mg per day. The respondents had good sleep quality was 44.7% while 55.3% had poor sleep. The study also found that there was a significant association between caffeine intake and sleep quality (p-value<0.01). Meanwhile, there was no significant association between sociodemographic characteristics and caffeine intake or sleep quality. This study shows that a student's excessive intake of caffeine is correlated with poor sleep quality. Therefore, prevention strategies should be used to raise awareness of the issue and understand how consuming too much caffeine might result in poor sleep quality.